Zirconium oxide / aramid fiber composite nanofiber membrane with high heat insulation and flame retardance and preparation method of zirconium oxide / aramid fiber composite nanofiber membrane

By adding nanozirconia to the aramid nanofiber synthesis process to form a zirconia/aramid composite nanofiber membrane, the problem of insufficient flame retardant performance of existing thermal insulation materials is solved, and high heat insulation and flame retardant performance is achieved, which broadens its application areas.

CN119571661APending Publication Date: 2025-03-07CHAMBROAD CHEM IND RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788359.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing thermal insulation materials have shortcomings in flame retardant properties, limiting their wide application in the construction and aviation fields.

Method used

By adding nanozirconia to the synthesis of aramid nanofibers, a zirconia/aramid composite nanofiber membrane is formed, which improves its high temperature resistance, heat insulation and flame retardant properties.

Benefits of technology

The composite film significantly improves the heat insulation and flame retardant effects of aramid fiber, broadens the application market for thermal insulation materials, and shows excellent performance in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571661A_ABST
    Figure CN119571661A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high-heat-insulation and flame-retardant-resistant composite materials, in particular to a high-heat-insulation and flame-retardant-resistant zirconium oxide / aramid fiber composite nanofiber membrane and a preparation method thereof. According to the technical scheme, nano zirconium oxide is added in the aramid nanofiber polymerization process, so that the nano zirconium oxide and aramid fibers are combined more tightly, firmly and uniformly, the obtained zirconium oxide / aramid composite nanofiber membrane has the excellent performance of high temperature resistance, high heat insulation, flame retardance, low thermal expansion coefficient and the like, and the application market of heat insulation materials can be greatly widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of high heat insulation and flame retardant composite materials, and in particular to a high heat insulation and flame retardant zirconium oxide / aramid composite nanofiber membrane and a preparation method thereof. Background Art

[0002] Thermal insulation materials are an effective means to reduce heat loss and improve energy utilization, which can effectively save energy. At present, the demand for the comprehensive performance of thermal insulation materials is getting higher and higher, and the flame retardant performance of thermal insulation materials has always been one of the bottlenecks restricting its application. Composite materials with both thermal insulation and flame retardant properties will be of great significance to the construction and air conditioning fields. Organic-inorganic composites are an effective means of modifying materials. Through the hybridization of multiple components, composite materials can be given more comprehensive performance and functions to meet certain special applications.

[0003] Aramid fiber is an organic fiber with extended molecular configuration axis, neat molecular arrangement, high crystallinity and high orientation. It has excellent characteristics such as high specific strength, high specific modulus, low density, low thermal expansion coefficient, low thermal conductivity, good dimensional stability, chemical corrosion resistance, thermal stability, etc. It also has good shock absorption, impact resistance, fatigue resistance, shear and abrasion resistance, electrical insulation and flame retardant properties. Aramid nanofiber combines the thermal stability, high crystallinity and good mechanical strength and chemical stability of aramid with the small size advantage of nanofiber, and is an excellent nanomaterial.

[0004] Zirconia ceramics are resistant to high temperatures and corrosion, and are insoluble in water and inorganic acids. The melting point of pure zirconia can reach 2700°C, and it is resistant to acid and alkali corrosion. At the same time, zirconia also has the characteristics of high resistance, low thermal conductivity and low thermal expansion coefficient. Chemically stable zirconia has been successfully used in high temperature resistant coatings and insulating materials. Summary of the invention

[0005] Based on the above content, the present invention aims to provide a highly thermally insulating, flame-retardant zirconia / aramid composite nanofiber membrane and a preparation method thereof. The technical solution of the present invention is to add nano-zirconia during the polymerization process of aramid nanofibers to make the combination between the aramid fibers tighter, firmer and more uniform. The obtained zirconia / aramid composite nanofiber membrane has excellent properties such as high temperature resistance, high thermal insulation, flame resistance, and low thermal expansion coefficient, which can greatly broaden the application market of thermal insulation materials.

[0006] The specific technical solutions are as follows:

[0007] A highly heat-insulating, flame-retardant zirconium oxide / aramid composite nanofiber membrane and a preparation method thereof, comprising the following steps and process conditions:

[0008] a) using zirconium oxide as the third monomer, p-phenylenediamine and terephthaloyl chloride to perform low-temperature polymerization of zirconium oxide / aramid nanofibers to obtain a zirconium oxide / aramid nanofiber gel;

[0009] b) dispersing the zirconium oxide / aramid nanofiber gel obtained in step a) into fibers, and filtering to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake;

[0010] c) hot-pressing the zirconium oxide / aramid nanofiber hydrogel obtained in step b) into a film to obtain a zirconium oxide / aramid composite nanofiber membrane.

[0011] Preferably, the zirconium oxide / aramid nanofibers described in step a) are polymerized at low temperature in an N-methylpyrrolidone salt solution, and the solubilizing salt is a mixture of one or more of CaCl2 and LiCl in any proportion.

[0012] More preferably, the amount of the dissolution-aiding salt is 4-8 wt % of the N-methylpyrrolidone salt solution.

[0013] More preferably, the dissolution-aiding salt is added to the reactor of the N-methylpyrrolidone solution at a dissolution temperature of 100-130°C.

[0014] Preferably, in step a), the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1 to 1.05.

[0015] Preferably, the polymerization temperature in step a) is -2 to 3°C.

[0016] Preferably, in step a), the amount of zirconium oxide used is 10-30wt% of the mass of the zirconium oxide / aramid composite nanofiber membrane, and the size of the zirconium oxide is 10-40nm.

[0017] Preferably, in step a), zirconium oxide is added sequentially after p-phenylenediamine is added, and stirred for 10-20 minutes.

[0018] Preferably, the specific process of step b) dispersion fiberization is: firstly dispersing the zirconium oxide / aramid gel in N-methylpyrrolidone to make the gel swell; and then dispersing the swollen gel in deionized water.

[0019] More preferably, the mass ratio of zirconium oxide / aramid nanofiber gel to N-methylpyrrolidone during the gel swelling process is 1:5-15, and the stirring speed during the swelling process is 3000-5000 r / min.

[0020] More preferably, in step b), the mass ratio of the swollen gel to the deionized water is 0.1:1-4, and the swollen gel is dispersed in the deionized water at a stirring speed of 5000-6000 r / min.

[0021] Preferably, in step c), the temperature of the hot press is 100-130° C.; the pressure of the hot press is 10-100 KPa.

[0022] The beneficial effects of the present invention are:

[0023] In the present invention, zirconium oxide nanoparticles are used as the third monomer to participate in the synthesis of aramid nanofibers. Compared with the common physical mixing method, the scheme of the present invention makes the combination of zirconium oxide nanoparticles and aramid fibers more firm and uniform. Nano zirconium oxide itself has the characteristics of high temperature resistance and corrosion resistance, and also has the characteristics of high resistance, low thermal conductivity and low thermal expansion coefficient. Compared with simple aramid nanofibers, the prepared zirconium oxide / aramid composite nanofiber membrane retains the excellent toughness of aramid nanofibers themselves and further improves the heat resistance and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Example 1 Optical micrograph of zirconia / aramid nanofibers;

[0025] Figure 2 Optical SEM image of zirconia / aramid nanofiber of Example 1. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0027] Example 1

[0028] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, 6 g of CaCl2 was added as a dissolving salt while stirring, and the mixture was heated to 100°C to dissolve the dissolving salt. The mixture was heated for 30 min to completely dissolve the dissolving salt. Then, the mixture was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0°C. 2.163 g of p-phenylenediamine was added and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine. 0.47 g of nano zirconium oxide particles (10 nm) was added and the mixture was stirred continuously for 10 min. 4.06 g of terephthaloyl chloride was added and the mixture was stirred continuously until gelation occurred in the reaction system and then the stirring was stopped to obtain a zirconium oxide / aramid nanofiber gel.

[0029] (2) dispersing the gel obtained in step (1) in 500 mL of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 5000 r / min for 2 min; dispersing the swollen gel in 2 L of deionized water, stirring at a speed of 5000 r / min for 20 min to obtain a uniform and stable zirconium oxide / aramid nanofiber suspension; filtering the suspension and washing with water to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake.

[0030] (3) heating the hydrogel filter cake of step (2) to 100° C. and 20 KPa in a hot press to remove moisture and hot press to form a film with a mass of 3.89 g;

[0031] Example 2

[0032] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, and 2 g of CaCl2 and 4 g of LiCl were added as solubilizing salts under stirring, and the mixture was heated to 120° C. to dissolve the solubilizing salts, and heated for 30 min to completely dissolve the solubilizing salts; then, the mixture was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0° C., 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine; 0.705 g of nano zirconium oxide particles (20 nm) was added, and the mixture was stirred continuously for 10 min; 4.101 g of terephthaloyl chloride was added, and the stirring was continued until gelation occurred in the reaction system, and the stirring was stopped to obtain a zirconium oxide / aramid nanofiber gel;

[0033] (2) dispersing the gel obtained in step (1) in 800 mL of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 3000 r / min for 2 min; dispersing the swollen gel in 3.2 L of deionized water, stirring at a speed of 6000 r / min for 20 min to obtain a uniform and stable zirconium oxide / aramid nanofiber suspension; filtering the suspension and washing with water to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake.

[0034] (3) heating the hydrogel filter cake of step (2) to 120° C. and 40 KPa in a hot press to remove moisture and hot press to form a film with a mass of 4.35 g;

[0035] Example 3

[0036] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, 6 g of LiCl was added as a dissolving salt under stirring, and the mixture was heated to 110° C. to dissolve the dissolving salt, and heated for 30 min to completely dissolve the dissolving salt; the mixture was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0° C., 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine; 0.94 g of nano zirconium oxide particles (30 nm) was added, and the mixture was stirred continuously for 15 min; 4.1 g of terephthaloyl chloride was added, and the stirring was stopped after gelation appeared in the reaction system to obtain a zirconium oxide / aramid nanofiber gel;

[0037] (2) dispersing the gel obtained in step (1) in 500 mL of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 4000 r / min for 2 min; dispersing the swollen gel in 1.5 L of deionized water, stirring at a speed of 6000 r / min for 20 min to obtain a uniform and stable zirconium oxide / aramid nanofiber suspension; filtering the suspension and washing with water to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake.

[0038] (3) heating the hydrogel filter cake of step (2) to 130° C. and 50 KPa in a hot press to remove moisture and hot press to form a film with a mass of 4.82 g;

[0039] Example 4

[0040] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, and 4 g of CaCl2 and 2 g of LiCl were added as solubilizing salts under stirring. The reaction vessel was heated to 115°C to dissolve the solubilizing salts, and the mixture was heated for 30 min to completely dissolve the solubilizing salts. The reaction vessel was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0°C. 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine. 1.12 g of nano zirconium oxide particles (40 nm) were added, and the mixture was stirred continuously for 15 min. 4.141 g of terephthaloyl chloride was added, and the mixture was stirred continuously until gelation occurred in the reaction system, and the stirring was stopped to obtain a zirconium oxide / aramid nanofiber gel.

[0041] (2) Dispersing the zirconium oxide / aramid gel obtained in step (1) in 1L of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 3000 r / min for 2 min; dispersing the swollen gel in 1L of deionized water, stirring at a speed of 5000 r / min for 20 min to obtain a uniform and stable zirconium oxide / aramid nanofiber suspension; filtering the suspension and washing with water to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake.

[0042] (3) The hydrogel filter cake of step (2) was heated to 125° C. and a pressure of 60 KPa in a hot press to remove moisture and hot press to form a film with a mass of 5.24 g.

[0043] Example 5

[0044] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, and 4 g of CaCl2 and 2 g of LiCl were added as solubilizing salts under stirring. The reaction vessel was heated to 110°C to dissolve the solubilizing salts, and the mixture was heated for 30 min to completely dissolve the solubilizing salts. The reaction vessel was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0°C. 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine. 1.41 g of nano zirconium oxide particles (30 nm) was added, and the mixture was stirred continuously for 15 min. 4.141 g of terephthaloyl chloride was added, and the mixture was stirred continuously until gelation occurred in the reaction system, and the stirring was stopped to obtain a zirconium oxide / aramid nanofiber gel.

[0045] (2) Dispersing the gel obtained in step (1) in 1 L of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 3000 r / min for 2 min; dispersing the swollen gel in 4 L of deionized water, stirring at a speed of 5000 r / min for 20 min to obtain a uniform and stable zirconium oxide / aramid nanofiber suspension; filtering the suspension and washing with water to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake.

[0046] (3) heating the hydrogel filter cake of step (2) to 125° C. and 60 KPa in a hot press to remove moisture and hot press to form a film with a mass of 5.89 g;

[0047] Comparative Example 1

[0048] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, and 5 g of CaCl2 and 1 g of LiCl were added as solubilizing salts under stirring, and the mixture was heated to 100° C. to dissolve the solubilizing salts, and heated for 30 min to completely dissolve the solubilizing salts; the mixture was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to 0° C., 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously and reacted for 30 min to completely dissolve the p-phenylenediamine; 4.06 g of terephthaloyl chloride was added, and the stirring was continued until gelation occurred in the reaction system, and the stirring was stopped to obtain aramid gel;

[0049] (2) dispersing the aramid gel obtained in step (1) in 500 mL of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 5000 r / min for 2 min; dispersing the swollen gel in 2 L of deionized water, stirring at a speed of 5000 r / min for 20 min to obtain a uniform and stable aramid nanofiber suspension; filtering the suspension and washing with water to obtain an aramid nanofiber hydrogel filter cake;

[0050] (7) The hydrogel filter cake of step (6) was heated to 110° C. and 100 KPa in a hot press to remove moisture and form a film by hot pressing. The mass of the film was 3.51 g.

[0051] Comparative Example 2

[0052] (1) Under nitrogen protection, 100 mL of anhydrous N-methylpyrrolidone (NMP) was added to a reaction vessel, and 3 g of CaCl2 and 3 g of LiCl were added as solubilizing salts under stirring. The reaction vessel was heated to 105° C. to dissolve the solubilizing salts, and heated for 30 min to completely dissolve the solubilizing salts. The reaction vessel was cooled in a cold water bath for 20 min to reduce the temperature of the salt solution in the reactor to −2° C. 2.163 g of p-phenylenediamine was added, and the mixture was stirred continuously for 30 min to completely dissolve the p-phenylenediamine. 4.08 g of terephthaloyl chloride was added, and the mixture was stirred continuously until gelation occurred in the reaction system, and then the stirring was stopped to obtain aramid gel.

[0053] (2) Dispersing the aramid gel obtained in step (1) in 500 mL of anhydrous N-methylpyrrolidone to swell the gel, stirring at a speed of 5000 r / min for 2 min; dispersing the swollen gel in 2 L of deionized water, stirring at a speed of 5000 r / min for 20 min, to obtain a uniform and stable aramid nanofiber suspension.

[0054] (3) Add 0.705 g of nano zirconium oxide particles (20 nm), stir at 5000 r / min for 20 min, and obtain a uniform and stable zirconium oxide / aramid nanofiber suspension.

[0055] (4) filtering and washing the suspension obtained in step (3), wherein most of the zirconium oxide nanoparticles are lost during the filtering and washing process, and obtaining a zirconium oxide-aramid nanofiber physically dispersed hydrogel filter cake;

[0056] (5) heating the hydrogel filter cake of step (4) to 120° C. and 50 KPa in a hot press to remove moisture and hot press to form a film with a mass of 3.62 g;

[0057] Performance Testing:

[0058] The zirconia / aramid nanofiber membranes provided in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests, and the test items included thermal conductivity (according to GB / T 42919.1-2023), heat release characteristics (according to ASTM D7309-21b "Standard Test Method for Determining Flammability Characteristics of Plastics and Other Solid Materials Using Microscale Combustion Calorimetry"), and flame retardancy. Among them, the thermal conductivity was determined using a TPS2500s thermal conductivity meter, the heat release characteristics were tested using a PL-180 microcalorimeter, and the flame retardancy was determined based on the heat release rate.

[0059] The test results are shown in Table 1:

[0060] Table 1 Performance test data of each embodiment and comparative example

[0061]

[0062] By comparing the test data in Table 1, it can be seen that the thermal conductivity of the nano-zirconia / aramid nanofiber membrane is significantly lower than that of the aramid fiber membrane without zirconium oxide added, and the zirconium oxide / aramid nanofiber membrane has excellent thermal insulation performance; after the comparative example 2 was filtered and washed after dispersion, most of the zirconium oxide nanoparticles were lost, and the performance was similar to that of the sample in comparative example 1; the total heat released by the zirconium oxide / aramid nanofiber membrane was reduced by one order of magnitude compared with that of comparative example 1 and comparative example 2. It can be seen that the zirconium oxide / aramid nanofiber membrane releases less heat during combustion and has excellent flame retardant effect. Figure 1 and Figure 2 The results of the observation of zirconium oxide / aramid nanofibers under optical microscope and scanning electron microscope in Example 1 are as follows: Figure 1 and Figure 2 It can be clearly observed that the nano-zirconia has been embedded in the aramid nanofiber network structure as an embedding body. In summary, the present invention provides a highly heat-insulating and flame-retardant zirconia / aramid nanofiber membrane, which can significantly improve the heat-insulating and flame-retardant effects of aramid fibers, and can enable aramid fibers to be widely used in thermal insulation materials.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly heat-insulating, flame-retardant zirconium oxide / aramid composite nanofiber membrane, characterized in that: The following steps are involved: a) using zirconium oxide as the third monomer, p-phenylenediamine and terephthaloyl chloride to perform low-temperature polymerization of zirconium oxide / aramid nanofibers to obtain a zirconium oxide / aramid nanofiber gel; b) dispersing the zirconium oxide / aramid nanofiber gel obtained in step a) into fibers, and filtering to obtain a zirconium oxide / aramid nanofiber hydrogel filter cake; c) hot-pressing the zirconium oxide / aramid nanofiber hydrogel obtained in step b) into a film to obtain a zirconium oxide / aramid nanofiber composite membrane; In step a), the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1:1 to 1.05; In step a), the amount of zirconium oxide used is 10-30wt% of the mass of the zirconium oxide / aramid composite nanofiber membrane.

2. The method for preparing the highly heat-insulating, flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: The zirconium oxide / aramid nanofibers described in step a) are polymerized at low temperature in an N-methylpyrrolidone salt solution, and the solubilizing salt is a mixture of one or more of CaCl2 and LiCl in any proportion.

3. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 2, characterized in that: The dosage of the dissolution-aiding salt is 4-8 wt % of the N-methylpyrrolidone salt solution.

4. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: The polymerization temperature in step a) is -2 to 3°C.

5. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: The size of the zirconium oxide is 10-40nm.

6. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: In step a), zirconium oxide is added sequentially after p-phenylenediamine is added, and stirred for 10-20 minutes.

7. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: The specific process of step b) dispersion fiberization is as follows: firstly, the zirconium oxide / aramid gel is dispersed in N-methylpyrrolidone to make the gel swell; and then the swollen gel is dispersed in deionized water.

8. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: During the gel swelling process, the mass ratio of zirconium oxide / aramid nanofiber gel to N-methylpyrrolidone is 1:5-15, and the stirring speed during the swelling process is 3000-5000 r / min; in step b), the mass ratio of the swollen gel to deionized water is 0.1:1-4, and the swollen gel is dispersed in deionized water at a stirring speed of 5000-6000 r / min.

9. The method for preparing the highly heat-insulating and flame-retardant zirconium oxide / aramid composite nanofiber membrane according to claim 1, characterized in that: In step c), the temperature of the hot press is 100-130° C.; the pressure of the hot press is 10-100 KPa.

10. Zirconia / aramid composite nanofiber membrane prepared according to the method according to any one of claims 1 to 9.